Solitonski snovni valovi v Bose-Einsteinovih kondenzatih - Arh, Tina (Matrika, 2018)
This article discusses solitary matter-waves in Bose-Einstein condensates, a nonlinear phenomenon that exhibits soliton-like properties. It starts with the theoretical description of condensate behaviour by the mean-field GrossPitaevskii equation, explores its collapse instabilities and shows the exact soliton solution in the 1D limit. In the experiments, the residual three-dimensionality and external potentials alter the fundamental soliton properties and introduce interesting new effects. The second part of the article focuses on the experimental formation of single and multiple stable solitary waves and solitary wave collisions. In conclusion some examples of possible applications are given.
Keywords: Bose-Einstein condensation; Bose-Einsteinova kondenzacija; kvantna statistična mehanika; quantum statistical mechanics; solitary matter waves; solitoni; solitons; solitonski snovni valovi